The bonds that impede: a model of the joint evolution of corruption and apathy - Varoufakis, Yanis (2006)
This paper discusses the joint evolution of corruption and public engagement in politics by means of a model combining psychological game theory with evolutionary game theory. Its contribution is to demonstrate that, while power corrupts and corruption undermines the legitimacy of power, the prospects for social and economic development may depend crucially on the evolution of an appropriate web of expectations, rather than on a powerful coercive mechanism that forces corruption underground. The theoretical results emphasise the context-specificity of corruption, explain resistance-to-corruption as a response to preferences inhabiting the ill-defined space between the walls separating one citizen from an `other', and links the evolution of corruption to the evolution of public spiritedness and the reach of participatory politics. - Reproduced.
Keywords: Corruption